Expression of a Deschampsia antarctica Desv. Polypeptide with Lipase Activity in a Pichia pastoris Vector - Claudia Rabert; Ana Gutiérrez-Moraga; Alejandro Navarrete; Darío Navarrete-Campos; León Bravo; Manuel Gidekel (International Journal of Molecular Sciences, 2014)
The current study isolated and characterized the Lip3F9 polypeptide sequence of Deschampsia antarctica Desv. (GeneBank Accession Number JX846628), which was found to be comprised of 291 base pairs and was, moreover, expressed in Pichia pastoris X-33 cells. The enzyme was secreted after 24 h of P. pastoris culture incubation and through induction with methanol. The expressed protein showed maximum lipase activity (35 U/L) with an optimal temperature of 37 °C. The lipase-expressed enzyme lost 50% of its specific activity at 25 °C, a behavior characteristic of a psychrotolerant enzyme. Recombinant enzyme activity was measured in the presence of ionic and non-ionic detergents, and a decrease in enzyme activity was detected for all concentrations of ionic and non-ionic detergents assessed.